The influence of understanding financial literacy, perceived ease of users, and consumptive lifestyles on the use of Shopee paylater (to student in the special region of Yogyakarta) - Sutarni, Sutarni; Dimas, Syifa Shabihah (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
The purpose of this study was to find out whether financial literacy has a positive and significant effect on the use of Shopee Paylater, to find out whether user convenience has a positive and significant effect on the use of Shopee Paylater and whether the consumptive lifestyle has a positive and significant effect on the use of Shopee Paylater. This research uses quantitative research methods. The data used in this study are primary data and secondary data. The data analysis technique used is Partial Least Square (PLS) analysis. The PLS measurement model consists of three main elements: the outer model, the goodness of fit criteria, and the inner model. Then the results show that financial literacy has a positive and significant effect on the use of Shopee Paylater, ease of use has a positive and significant effect on the use of Shopee Paylater, and a consumptive lifestyle has a positive and significant effect on the use of Shopee Paylater for students in the Special Region of Yogyakarta.